Śmierć na ulicach Krakowa w latach 1945–1947 w materiale archiwalnym krakowskiego Zakładu Medycyny Sądowej - Konopka, Tomasz (Pamięć i Sprawiedliwość, 2005)
The article presents the results of a research on reports of autopsy carried out in the Cracov’s Institute of Forensic Medicine at the turbulent postwar time. An occasion to publish this material is the 200th anniversary of foundation of the Cracov Department of Forensic Medicine. The collection of autopsy reports contains more or less detailed descriptions of the cause of death of at least 72 people killed by UB and Militia functionaries in fight, during a police chase or by “accident”. Some of the victims were known for writing about non-communist resistance units.There are some precise descriptions of injuries, which had been received by people who were killed or who committed suicide in prison, indicating brutal beating and tortures to death. During the first year after the liberation of Cracov the Institute performed an autopsy on 25 bodies of people killed for unknown reasons or brutally murdered in assaults by Soviet soldiers who were stationed in the town. The Cracov prisons sent in cadavers ofthose whose health was ruined by hard prison conditions. In March 1945 groups of approximately 8 corpses were found on fields around Cracov, no traumatic cause of death was noted. Its is probable that those bodies had been left behind by transports taking the prisoners away during a mass NKVD’s action. The Institute examined also 36 corpses of functionaries who died fighting or were assassinated and corpses of random victims of gunfights.Amongst three hundred more or less anonymous people who died in the streets of Cracov during those years, there were wildly known cases, like the assassination of Narcyz Wiatr “Zawojna” shot in the Planty by the UB, Ró˝a Berger killed during anti-Semiticriots, and the case of a brutally murdered prosecuting attorney Roman Martini who had been carrying out a secret inquiry into Katyn.